Hvidoere Smiley Faces: International diabetes quality of life assessment tool for young children. Issue 3 (22nd November 2017) - Hoey, Hilary; Lange, Karin; Skinner, TC; Mortensen, Henrik; Swift, Peter; Aanstoot, Henk‐Jan; Castaňo, Luis; Cameron, Fergus; de Beaufort, Carine; ,
Abstract : Background: Few diabetes‐specific quality of life (QOL) tools are available for young children. Objectives: To design and evaluate, a new age‐specific QOL questionnaire and its associations with treatment regimens and metabolic control. Methods: Clinical, demographic data and centrally analyzed HbA1c were collected on 1133 children <11 years (girls 48%; mean ± SD age 8.0 ± 2.1 years; diabetes duration ≥1 year) from 18 centers (Europe, Japan, North America and Australia). Children completed the 10‐item Smiley Faces QOL questionnaire constructed for the study, and children ≥7 years also completed the KIDSCREEN‐10 Index. Results: In total, 1035 children completed the new Smiley Faces questionnaire which was well understood by 993 (70% ≥4 years and 96% ≥5 years, respectively). Internal consistency and reliability were good (Cronbach's α = .73). Inter‐item correlation ranged r = 0.047 to 0.451 indicating each item measures separate aspects of children's satisfaction construct. Convergent validity assessed by comparison to the HrQOL KIDSCREEN‐10 Index showed moderate correlation coefficient 0.501. Factor analysis revealed 3 factors explaining 51% of the variance. Children reported good QOL with most items positive, mean values between 1 and 2 on a 5‐point scale (lower scores indicating greater QOL). Diabetes satisfaction was unrelated to age, diabetes duration, HbA1c, or severe hypoglycemia. Girls were more satisfied than boys. Children on intensive regimens reported better QOL ( P < .02). Main dissatisfaction related to insulin injections and blood sugar testing. Conclusions: The Smiley Faces questionnaire enables QOL assessment in young children and identification of areas of dissatisfaction and other clinically relevant items relating to diabetes management.